Changes in Serum Estradiol Levels and Histomorphological-Evaluation of Cortical Thickness in Long Bones of Mice Induced by Anastrazole and Protective Effect of Olive Oil - Ishaq, Anjum (International Journal of Pathology, 2023)
Background:Breast cancer is the second major cause of death among women worldwide. Drugs like anastrazole are effective standardized therapy for postmenopausal breast cancer patients. Anastrazole causes estrogen deficiency by inhibiting enzyme Aromatase. Estrogen has an important dynamic role in growth as well as development of bone, both in men and women. Olive oil can be used as non-hormonal therapy to improve skeletal health by maintaining bone mineral density in patients taking anastrazole. Objective: The aim of this study was to find out protective effect of olive oil in bone loss induced by the use of anastrazole. Materials and Methods: Sixty female albino mice, 6-8 weeks of age were used in this experimental study. Aromatase inhibitor drug anastrazole was given alone and in combination with olive oil once daily for 30 consecutive days. Mice were divided into three groups.Group 1(Control group) which were given normal diet only, Group 2 (Drugged mice group) and Group 3 (Drugged + Olive oil group). Blood samples were taken by cardiac puncture and ECLIAmethod was used for serum estradiol estimation. Femur bone specimens were obtained and examined for histomorphological evaluation of cortical thickness.Study duration was from March –December 2019. Results: Different parameters of all the groups were measured before and after experiment. After experiment, group 1mice showed increased levels of serum estradiol (18.25± 5.01pg/ml), as compared to group 2 (9.21± 2.12pg/ml) and group 3mice (14.79± 2.53pg/ml). Group 1 mice had femur weight of 0.08 ± 0.01 grams as compared to group 2 (0.05± 0.006 grams)and group 3mice (0.07± 0.008 grams). Mean cortical thickness of group 1 mice was (273.00 ± 15.67µm), that of group 2 was (138.00± 19.89µm), and that of group 3 mice was (189.50±14.31µm). Conclusion: The results showed beneficial and protective effects of olive oil in anastrazole induced bone loss in female albino mice.